MRI features and preliminary diagnostic assessment using large language models of cystic tumor progression mimicking radiation necrosis in brain metastasis patients treated with immunotherapy: case report - Tan, Guirong; Cai, Mingchen; Lu, Yu; Liu, Amy; Li, Shimin; Xiao, Gang; Zhong, Lijuan; Li, Lijia; Hu, Yichuan; Liang, Qiong; Jiang, Haihui; Liu, Xiang; et al. (Frontiers in Immunology, 2025)
The application of immunotherapy in patients with brain metastasis (BM) has increased rapidly in recent years, which led to a diagnostic dilemma between pseudoprogression and true progression in the post-treatment evaluation. Here, we reported MRI characteristics of pathology-confirmed large cystic rim-enhancing lesions of tumor progression in two BM cases with immunotherapy treatment, which mimicked radiation necrosis on conventional MRI. In addition, our preliminary findings showed that the custom large language models (LLMs) using ChatGPT and DeepSeek yielded correct diagnoses in these cases, which may suggest the potential utility of LLMs for the decision-making in this field.